2015
DOI: 10.1074/jbc.m115.647180
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Precursor-like Protein 2 and Sortilin Do Not Regulate the PCSK9 Convertase-mediated Low Density Lipoprotein Receptor Degradation but Interact with Each Other

Abstract: Background: It was reported that amyloid precursor-like protein 2 (APLP2) increases PCSK9-mediated low-density lipoprotein receptor (LDLR) degradation, and sortilin facilitates PCSK9 secretion. Results: APLP2 or sortilin deficiency/overexpression in cells/mice did not affect LDLR degradation by PCSK9. However, APLP2 binds sortilin, and PCSK9 enhances their degradation. Conclusion: APLP2/sortilin are not required for PCSK9 activity on LDLR, but their interaction may modulate APLP2 functions. Significance: APLP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 62 publications
5
52
2
Order By: Relevance
“…Recently, two proteins were suggested to enhance PCSK9-mediated degradation of the LDL receptor: one is sortilin, which binds to PCSK9 in the trans-Golgi network and possibly facilitates its secretion 37) , and the other is amyloid precursor-like protein 2 (APLP2), which facilitates trafficking of the PCSK9-LDL receptor complex to endosomes/lysosomes 38) . However, Butkinaree et al 39) reported that PCSK9 enhanced LDL receptor degradation independent of sortilin or APLP2 ex vivo The present study has several limitations. First, it was a post hoc analysis of the TRUTH trial and all subjects had CAD.…”
Section: Discussionmentioning
confidence: 62%
“…Recently, two proteins were suggested to enhance PCSK9-mediated degradation of the LDL receptor: one is sortilin, which binds to PCSK9 in the trans-Golgi network and possibly facilitates its secretion 37) , and the other is amyloid precursor-like protein 2 (APLP2), which facilitates trafficking of the PCSK9-LDL receptor complex to endosomes/lysosomes 38) . However, Butkinaree et al 39) reported that PCSK9 enhanced LDL receptor degradation independent of sortilin or APLP2 ex vivo The present study has several limitations. First, it was a post hoc analysis of the TRUTH trial and all subjects had CAD.…”
Section: Discussionmentioning
confidence: 62%
“…7D ) but remained stable in WT livers. A similar observation was done with Pcsk9 +/ Ϫ (heterozygote) mice that presented a 70% drop in circulating PCSK9 levels, likely due to a concomitant increase in LDLR levels ( 42 ). Whether this unexpected accumulation of surface LDLR in WT mice fed a high-cholesterol diet contributes to the protection of vessel walls by clearing the excess of circulating cholesterol remains to be verifi ed.…”
Section: Synergistic Effect Of Ovariectomy and Pcsk9 Defi Ciency On Pmentioning
confidence: 74%
“…was challenged in a recent report, which found APLP2 was not involved in PCSK9-mediated degradation of LDLR ( 37 ). The fi nding of DeVay and coworkers ( 34,35 ) of most relevance to our work was that an anti-PCSK9 antibody was transported with PCSK9 to lysosomes by the APLP2-mediated pathway.…”
Section: Proteolytic Cleavage Of Pcsk9 Slows the CL Of Ly From Serummentioning
confidence: 41%